Comparison of Cardiac and Renal Involvement in Patients with Abdominal Aortic Aneurysm and Aorto-Illiac Occlusive Diseases who Underwent Elective Vascular Surgery - I., Botchorishvili; N., Sharashidze; N., Pargalava; Z., Pagava; G., Saatashvili (European Scientific Journal, ESJ, 2017)
Objective: The aim of this study is to assess comorbidities such as risk factors between patients with AAA and AIOD who underwent elective surgery. Abdominal Aortic Aneurysm (AAA) as well as Aorto-Illiac Occlusive Diseases (AOID) is a major risk to health. Comorbidities, during these conditions, play an important role in clinical course and the outcome of the diseases. Material and Methods: We studied 373 patients, 124 of them with AAA and 249 patients with AIOD. Age, gender, smoking status, hypertension, and dyslipidemia were assessed. Also, Glomerular Filtration Rate (GFR) was calculated for all patients. The history of Diabetes Mellitus (DM) was identified. The coexistence of Ischemic Heart Disease (IHD) was diagnosed according to clinical history or electrocardiographic and ultrasound criteria. In addition, Transthoracic Echocardiography (TTE) examination was performed for all patients. Results: Out of 373 patients, a gender majority of them were male (94% in AIOD and 90% in AAA). Patients with AIOD were younger than patients with AAA (63.69 ± 8.219 and 67.90 ± 8.810 P= 0.0000, repectively). The prevalence of Hypertension (HT) was less in AOID and then in AAA. Diabetes mellitus (DM) was more prevalent in AIOD patients. Rate of Coronary Artery Disease (CAD) and Coronary Revascularization did not differ between groups. The prevalence of Left Ventricular Hypertrophy was lower in AIOD group (50.4% in AIOD vs 64.8% in AAA P=0.0084). Rate of GFR ? 60 was found to be lower in AIOD group than in AAA group (20.16% vs 49.6% P=0.0000). Higher prevalence rate of Aortic Valve diseases of Aorta in patients with AAA was found (17.3% in AIOD vs 45.6% in AAA P=0.0000). Conclusion: Higher prevalence rate of Aortic Valve diseases in patients with AAA was found. However, this association may be determined by the same factors that are responsible for inflammatory and degenerative changes in grate vessels in aneurismal disease. High rate of LVH and RF in AAA group indicates unfavorable risk profile in patients with AAA.